Re-imaginando la clínica jurídica de derechos humanos - Carrillo, Arturo J. (2013)
"Original published in English in: Carrillo, Arturo J. and Nicolás E. Yaksic, Re-imagining "The Human Rights Law Clinic", in Maryland Journal of International Law, no. 26, pp. 80/112, 2011. Available at: https://digitalcommons.law.umaryland.edu/mjil/vol26/iss1/7/. -- Translation: María Virginia Deymonnaz. Review: Federico De Fazio". ? There are experiences that provide alternative perspectives on how best to configure a human rights clinic. One of these is provided by the proliferation of public interest and human rights (PIHR) law clinics (clínicas jurídicas de interés público y derechos humanos) in several Latin American countries. The goal of the article is to contribute to the debate on the best ways to pursue social justice through clinical education by importing a number of relevant insights drawn from the Latin American experience of the PIHR law clinics. The article also advances an original perspective: That a successful trajectory of these home-grown clinics in countries like Argentina, Chile, and Colombia can be contrasted constructively with the development of their counter parts at law schools in the United States. Several of the lessons learned from this Latin American model, it will be argued, are relevant to the addressing the methodological challenges described.